AI-POWERED RESTORATION OF VINTAGE FILMS INTO NEW CINEMA: HARMONIZING CREATION AND AUTOMATION - R, Sathiamoorthy; B, Senthil Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The revival of classic films has made significant progress thanks to Artificial Intelligence-powered restoration methods. The AI produces a restored film with improved brightness, resolution and color while preserving the original film content through complex algorithms. The purpose of the research is to analyze the opinions of viewers and historians about films restored with artificial intelligence and to address the ethical issues associated with AI restoration. Data was collected on likes and dislikes of viewers of AI-restored movies on YouTube, and the survey analyzed 375 people watching the vintage movie and its restored version. Analysis results show that AI-restored movies have better resolution, color and sound quality than the original vintage footage. Historians argue that AI algorithms can change the historical meaning and authenticity of the original work and undermine the original artistic intent of old films. The difficulty with artificial intelligence is finding a balance between technical progress and maintaining creative and historical integrity, which requires strict ethical standards to prevent potential harm. Preserving the integrity and true historical accuracy of original content and maintaining public trust require transparent practices, rigorous authentication procedures, and careful navigation of copyright, ownership, and consent issues. The rights of content producers, communities and individuals must be respected to ensure that AI-assisted restoration is carried out responsibly and ethically. The power of artificial intelligence in the restoration of old films has great potential to preserve and celebrate our film heritage.